PROFESSIONAL DEVELOPMENT OF A TEACHER IN HIGHER EDUCATION - Sergeeva, Marina; Klychkov, Kirill; Lukashenko, Dmitry; Petrova, Leila; Ilenko, Natalya (Revista Inclusiones, 2020)
The article examines the professional development of a teacher in higher education based on the example of a powerlifting trainer in a specialized university sports center. The relevance of the research topic is determined by the need to resolve the issues of professional development of a powerlifting trainer of a specialized university sports center in modern social and economic conditions, characterized by the orientation of the government towards the modernization of additional education with particular emphasis on the quality of professional training, retraining, and advanced training of sports trainers. The issues of professional development of powerlifting trainers require a systemic psychological and pedagogical approach that also accounts for the cultural, social, and other patterns involved in personality development and determining the rules for the implementation of said development. The new times set new requirements for training professionals in powerlifting. Along with students, the trainer is considered one of the key subjects of activity in powerlifting. The assessment of the productivity of activity in powerlifting in the modern reality of world-level development and its socio-economic and political significance appears to be quite a complicated task both from a pragmatic viewpoint and in accordance with the main life, humanistic, and philosophical principles. The specific features of the social functions and professional activity of powerlifting trainers condition the problem of their professional development, which appears especially relevant. The essence of this development seems in a fundamental restructuring of the entire system of professional and pedagogical education based on the ideas and methods of other sciences.